2020
DOI: 10.1186/s13195-020-00701-7
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric symptoms in at-risk groups for AD dementia and their association with worry and AD biomarkers—results from the DELCODE study

Abstract: Background Early identification of individuals at risk of dementia is mandatory to implement prevention strategies and design clinical trials that target early disease stages. Subjective cognitive decline (SCD) and neuropsychiatric symptoms (NPS) have been proposed as potential markers for early manifestation of Alzheimer’s disease (AD). We aimed to investigate the frequency of NPS in SCD, in other at-risk groups, in healthy controls (CO), and in AD patients, and to test the association of NPS with AD biomarke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…Another future direction would be to analyze networks of impulse dyscontrol in MCI and SCD separately. A recent study showed that the Neuropsychiatric Inventory-Questionnaire domains associated with impulse dyscontrol -namely, agitation/aggressiveness, aberrant motor behavior and appetite disturbances (Ismail et al, 2016) -were more prevalent in MCI than in SCD (Sannemann et al, 2020). These discrepancies may be due to more substantial cognitive deficits in MCI and might even differ across MCI subgroups.…”
Section: Future Directionsmentioning
confidence: 99%
“…Another future direction would be to analyze networks of impulse dyscontrol in MCI and SCD separately. A recent study showed that the Neuropsychiatric Inventory-Questionnaire domains associated with impulse dyscontrol -namely, agitation/aggressiveness, aberrant motor behavior and appetite disturbances (Ismail et al, 2016) -were more prevalent in MCI than in SCD (Sannemann et al, 2020). These discrepancies may be due to more substantial cognitive deficits in MCI and might even differ across MCI subgroups.…”
Section: Future Directionsmentioning
confidence: 99%
“…6 The association between AD biomarkers and anxiety is supported in the literature, with three studies showing a relationship between decreased CSF Aβ 42 and anxiety. [47][48][49] The relationship between Aβ and depression is more uncertain. Some studies identified no relationship between decreased CSF Aβ 42 and increased depression in samples of mixed cognitive status; 47,48,50 others revealed interactions with mood disturbance in NC 49,51 and chronic subsyndromal depressive symptoms in MCI.…”
Section: Resultsmentioning
confidence: 99%
“…4749 The relationship between Aβ and depression is more uncertain. Some studies identified no relationship between decreased CSF Aβ 42 and increased depression in samples of mixed cognitive status; 47,48,50 others revealed interactions with mood disturbance in NC 49,51 and chronic subsyndromal depressive symptoms in MCI. 52 Plasma Aβ levels have been associated with depression, such that higher baseline plasma Aβ 42 was a predictor for first depressive episode in NC older adults, and progression to AD at 5 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 NPS are common across the clinical spectrum from mild cognitive impairment (MCI) to dementia, with 35-85% of patients with MCI and nearly all patients with dementia showing NPS. [1][2][3] NPS are associated with increased caregiver burden, higher costs of care, worse cognitive performance and poorer quality of life. [4][5][6][7] NPS also predict a worse prognosis including more rapid progression of cognitive and functional decline, earlier institutionalization and death.…”
Section: Introductionmentioning
confidence: 99%